Proactive Surveillance Approach to Guarantee a Functional Arteriovenous Fistula at First Dialysis is Worth. Issue 3 (May 2015) - Mufty, Hozan; Claes, Kathleen; Heye, Sam; Fourneau, Inge
Purpose: To evaluate the impact of a proactive surveillance program on functional access rate at the time of first dialysis. Methods: In January 2010, a proactive surveillance program to intercept failures to mature was set up at the University Hospitals Leuven. Patients receiving an arteriovenous fistula (AVF) for pre-dialysis end-stage renal disease between January 2010 and May 2013 were retrospectively analyzed. The primary end-point was a functional AVF at first dialysis. Also, AVF- associated complications and reinterventions were analyzed. Furthermore, primary, assisted primary and secondary patency rates were estimated using Kaplan-Meier survival curves. Results: One hundred sixty-four patients were included in the study. Patients were followed until first dialysis. Median follow-up time was 287 days (interquartile range, 108-551 days). During follow-up, 40 patients (24.4%) needed one or more additional interventions, resulting in 60 reinterventions. Ten patients needed dialysis within the minimal accepted maturation period of the AVF (4 weeks). Of the 154 patients who could await the maturation period of the AVF, 145 (94.2%) appeared ready for use at the time of dialysis or at the end of the study period. In 34 of them (22%), this was thanks to one or more interventions during follow-up. Conclusions: A dedicated surveillance program of patients with AVFs in the pre-dialysis stadium detects failure to mature. Close coaching and proactive intervention can aid the patient in his own "fistula first" project.